PENGARUH KUALITAS KOMUNIKASI PELAYANAN PUBLIK DALAM MENANGANI KOMPLAIN TERHADAP KEPUASAN PELANGGAN : Survei Pada Pelanggan PDAM Tirta Kahuripan Kabupaten Bogor - Zalfa Ainun Nafisa (2020)
This study discusses the influence of communication quality in handling complaints against customer satisfaction. The purpose of this study is to determine and measure whether there is an influence or not the quality of communication implemented by public services in handling complaints can affect customer satisfaction in PDAM. The theory used is the theory of Customer Relationship Management (CRM). The research method used is quantitative with an explanatory approach with data collection conducted by distributing questionnaires. The results of the study there is a fairly strong influence (R = 0.466) between the effect of quality of face-to-face communication with customer satisfaction of PDAM Tirta Kahuripan. Based on the calculation of the coefficient of determination results obtained the influence of variable X on variable Y by 21.7%. The results of the hypothesis test with t count of 5.207 which can be concluded that Ho is rejected and Ha is accepted, which means there is a significant influence between the influence of Communication Quality with Customer Satisfaction. The conclusion from the results of this study is that the implementation of quality face-to-face communication by public services in handling complaints can have a positive influence to cause increased satisfaction felt by customers. Keywords: Communication Quality, Customer Relationship Management, Customer Satisfaction